Optimal perturbation (Wo=15, Re_δ=530): snapshots in a (z,r)-cross-section - Duo Xu; Baofang Song; Marc Avila (PANGAEA, 2022)
The data are obtained via an in-house Matlab script (developed by Dr. Baofang Song) to compute the non-modal transient growth of disturbances in pulsatile and oscillatory pipe flows. In this study, a Newtonian fluid driven by pulsatile and oscillatory flow rate flows in a straight pipe. In pulsatile flow, there are three governing parameters: steady Reynolds number (defined by the steady flow component), pulsation amplitude (ratio of oscillatory and steady flow component) and Womersley number (dimensionless pulsation and oscillation frequency). In oscillatory flow, due to vanishment of steady flow component, oscillatory Reynolds number (defined by the oscillation flow component) and Womersley number. The Reynolds number defined by the thickness of Stokes layer is alternatively used for the oscillatory Reynolds number. The study was carried out in a manner that one governing parameter varies while other governing parameters are fixed. The data file extquotesingleOptimalPerturbation_ZRCros_Wo15_Redelta589.dat extquotesingle shows the time series of the three components of velocity and spanwise vorticity in the radial-radial cross-section, for the Reynolds number (defined with Stokes layer thickness) of 589 and Womersley number of 15. This file includes six columns: the first column indicates the streamwise coordinate; the second column indicates the radial coordinate; the third column indicates the radial component of velocity; the fourth column indicates the azimuthal component of velocity; the fifth column indicates the streamwise component of velocity; the sixth column indicates the spanwise vorticity.